Housing market dynamics under a pegged exchange rate – a study of Hong Kong - Yu, Ka Hung; Hui, Eddie Chi Man (International Journal of Strategic Property Management, 2018)
This study explores the major determinants of prices and rents of properties in the mass housing market and in the luxury housing market of Hong Kong. The findings show that property price (and rental) dynamics are primarily driven by demand factors, rather than by housing supply. While macroeconomic factors and the provision of subsidized homeownership, to varying degrees, influence housing prices and/or rents, it is the result of U.S. monetary policy which has directly (through changes in money supply) and indirectly (through the wealth effect from a bullish stock market fuelled by unconventional monetary policy such as Quantitative Easing (QE) triggered the current affordability issue. Some policy implications with reference to recent U.S. monetary policy developments as well as to the Linked Exchange Rate System between Hong Kong Dollar and U.S. Dollar are then discussed.